Breast Cancer Treatment Using the Magneto-Hyperthermia Technique Associated with Omega-3 Polyunsaturated Fatty Acids' Supplementation and Physical Training - Matheus Haubert Theinel; Mariana Penteado Nucci; Gabriela Cianciarullo; Fernando Anselmo Oliveira; Arielly da Hora Alves; Javier Bustamante Mamani; Gabriel Nery de Albuquerque Rego; Nicole Mastandrea Ennes do Valle; Olívia Furiama Metropolo Dias; Cícero Júlio Silva Costa; Felipe Lima Nascimento; Juan Matheus Munoz; et al. (MDPI AG, 2024)
Breast cancer (BC) presents a growing global concern, mainly for the female population of working age. Their pathophysiology shows challenges when attempting to ensure conventional treatment efficacy without adverse effects. This study aimed to evaluate the efficacy of magneto-hyperthermia (MHT) therapy associated with supplementation with omega-3 polyunsaturated fatty acid (w-3 PUFA) and engagement in physical training (PT) for the triple-negative BC (TNBC) model. First, we assessed the physicochemical properties of iron oxide nanoparticles (ION) in biological conditions, as well as their heating potential for MHT therapy. Then, a bioluminescence (BLI) evaluation of the best tumor growth conditions in the TNBC model (the quantity of implanted cells and time), as well as the efficacy of MHT therapy (5 consecutive days) associated with the previous administration of 8 weeks of w-3 PUFA and PT, was carried out. The results showed the good stability and potential of ION for MHT using 300 Gauss and 420 kHz. In the TNBC model, adequate tumor growth was observed after 14 days of 2 × 106 cells implantation by BLI. There was a delay in tumor growth in animals that received w-3 and PT and a significant decrease associated with MHT. This pioneering combination therapy approach (MHT, omega-3, and exercise) showed a positive effect on TNBC tumor reduction and demonstrated promise for pre-clinical and clinical studies in the future.